Rhizosphere P-Enzyme Activity, Mineral Nutrient Concentrations, and Microbial Community Structure Are Altered by Intra-Hole Cropping of Cowpea With Cereals - Jaiswal, Sanjay K.; Maredi, Mpelang P.; Dakora, Felix D. (Frontiers in Agronomy, 2021)
In Africa, intercropping and intra-hole cropping systems are a common practice used by smallholder farmers to optimize land use and tap the benefits of plant-to-plant interactions. The aim of this study was to evaluate mineral nutrient concentrations, P-enzyme activity and changes in microbial communities in the rhizospheres of sole cropped and intra-hole planted cowpea (cvs. TVu 546 and PAN 311), maize (cv. ZM 521) and sorghum (cv. M48). Cowpea cv. TVu546 intra-hole planted with sorghum (i.e. TVu546+M48) produced the highest rhizosphere acid phosphatase (APase) activity (230.0 μg p-nitrophenol.g-1soil.h-1). From 16S rRNA Miseq Illumina sequencing, the rhizosphere bacterial community structure was altered by intra-hole cropping, and dominated by Actinobacteria, Acidobacteria, Bacteroidetes, Firmicutes, Planctomycetes, Proteobacteria and Verrucomicrobia, which together accounted for about > 95% of the total sequences. The Sphingobacteria phylum was the dominant microbial group in the rhizosphere soil of all the cropping systems. The Proteobacteria phylum was the second most abundant in this study, which included the beneficial bacteria in all the rhizosphere soils studied. In contrast, typical pathogens like Ralsotonia and Agrobacterium were completely absent, indicating that the intra-hole cropping system can provide protection against soil-borne diseases possibly through elimination by antibiotics and/or phytoalexins present in plant and microbial exudates in the rhizosphere. Mucilaginibacter and Flavobacterium were however selectively present with intra-hole cropping.